Dynamic fuzzy neural networks : principles, algorithms and applications - Wu, Shi Qian. (2008)
The objective of this thesis is to develop FNN's by various techniques so that these systems can be used for on-line identification and control processes in dealing with nonlinear, time-varying, ill-defined systems.